Perspective on improving school quality: the influence of teamwork and curriculum effectiveness in Islamic schools - Fadhli, Muhammad; Prasetyo, Muhammad Angung Manumanoso; Siregar, Muhammad Fuad Zaini; Pasaribu, Mansyur Hidayat; Sari, Dwhy Dinda (Intelektual Pustaka Media Utama, 2024)
School quality is the most important aspect and a major issue in the education system. This research aims to explore the influence of teamwork and curriculum effectiveness on improving school quality. The method employed is based on a quantitative design with a survey approach. A questionnaire was used to collect data from 146 respondents. School quality is the key variable in this research. The data analysis was conducted using SmartPLS software to provide detailed information on the contribution of each variable's indicators. The findings of this research indicate a strong contribution from each variable in enhancing school quality. The R-square value for the curriculum effectiveness variable is 0.365, meaning that this variable contributes to a 36.5% improvement in school quality. On the other hand, the teamwork variable contributes 62.3% to school quality. These results clearly demonstrate the originality of this research, highlighting that teamwork in schools has a higher contribution value than curriculum effectiveness. The future research needs to examine how to establish teamwork in Islamic educational institutions as an effort to enhance quality.